A Staggered Grid Numerical Method for the Navier-Stokes Equation - Sudi Mungkasi (Journal of Natural A, 2014)
We consider incompressible fluid flows governed by the two-dimensional Navier-Stokes equation. The Navier-Stokes equation is solved numerically using a staggered grid finite difference method. Our aim in this paper is to assess the performance of this numerical method for the Navier-Stokes equation. The lid-driven cavity problem is taken into account to test the numerical method. In order to achieve our aim we focus on the motion of the fluid, and in particular, its velocity. Our results are compared with some available benchmark data. Keywords— finite difference method, lid-driven cavity flow, Navier-Stokes equation, staggered grid.